2019
DOI: 10.4103/ua.ua_37_18
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic characteristics of lower urinary tract of patients with idiopathic overactive bladder

Abstract: Aims:The aims of this study were to determine the frequency and clinical significance of individual urodynamic signs, which revealed on the basis of the results of comprehensive urodynamic examination of patients with the idiopathic overactive bladder (IOAB), to produce definitions of these features, and to describe any necessary remedial action.Materials and Methods:To identify the most common features and artifacts, we conducted a combined urodynamic examination of 137 patients with IOAB (105 women and 32 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
1
2
0
1
Order By: Relevance
“…Fan et al, 2011 the bladder volume at the first desire to void and cystometric capacity were lower in both men and women diagnosed with OAB and DO [8] . Also we agree with Dekhtiar YM, et al, 2019 who reported reduced maximum cystometric capacity in 75.9% OAB patients, reduced bladder sensation in 70.8% patients, and change in bladder compliance in 43.1% patients [10] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Fan et al, 2011 the bladder volume at the first desire to void and cystometric capacity were lower in both men and women diagnosed with OAB and DO [8] . Also we agree with Dekhtiar YM, et al, 2019 who reported reduced maximum cystometric capacity in 75.9% OAB patients, reduced bladder sensation in 70.8% patients, and change in bladder compliance in 43.1% patients [10] .…”
Section: Discussionsupporting
confidence: 92%
“…In comparison to Dekhtiar YM, et al, 2019 reported that 35.8% OAB patients, patients had detrusor overactivity during the whole period of bladder filling as a result of spontaneous detrusor contraction [10] .…”
Section: Discussionmentioning
confidence: 85%
“…Такие изменения в стенке МП приводят к ее денервации и усилению сократительной активности, а также повышенному выделению уротелием биологически активных веществ, стимулирующих афферентные нервные окончания в подслизистом слое МП, что в том и в другом случаях приводит к учащенному мочеиспусканию и формированию ГАМП. Ухудшение артериального кровотока, приводящее к ишемии детрузора, патогенетически обусловливает применение допплерографии сосудов детрузора в качестве метода разработки нового направления в лечении пациентов с ГАМП [25]. Authors' contribution.…”
Section: возможности допплерографического исследованияunclassified
“…Clinical relevance of IBS without DO is that it may also contribute to overactive bladder (OAB). Urodynamic nature, definition, and the frequency of IBS without DO is still uncertain . One recent study with 478 neurologic patients showed the frequency of IBS (defined as FS < 100 mL) with DO vs IBS (defined as FS < 100 mL) without DO is 156 (17.1%) vs 97 (10.6%), the latter being slightly more uncommon than the former .…”
Section: Introductionmentioning
confidence: 99%